Local cultural values and Islamic values: relevance and internalization for strengthening Religious Moderation - Umar, Mardan; Abdul Ziqron Mopoliu; Feiby Ismail (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
As a multicultural country, Indonesia has cultural diversity spread across regions. The local culture, which is one of the indicators of religious moderation, has noble values that can be the force for a peaceful and tolerant religious life. Cultural unity can be a tool for uniting different religious communities. Therefore, this study aims to analyze local cultural values and their relevance to Islamic values as strengthening religious moderation. The research uses a qualitative approach with data collection techniques through observations, interviews, and documentation. The results of this study show that local cultural values have relevance with Islamic values in support of strengthening religious moderation. Therefore, there needs to be an effort to strengthen religious Moderation in heterogeneous communities that is by internalizing local cultural value through: Religious Education, integration of religious-based cultural value in the activities of organizations and social institutions of society. The findings also suggest that greater attention be paid to local cultural development as a supportive factor in building a peaceful, moderate, and tolerant society.